Taxonomy and Phylogeny of Four New Species in Absidia (Cunninghamellaceae, Mucorales) From China - Zong, Tong-Kai; Zhao, Heng; Liu, Xiao-Ling; Ren, Li-Ying; Zhao, Chang-Lin; Liu, Xiao-Yong (Frontiers in Microbiology, 2021)
Four new species within the genus Absidia, A. globospora, A. medulla, A. turgida, and A. zonata, are proposed based on a combination of morphological traits, physiological features, and molecular evidences. A. globospora is characterized by globose sporangiospores, a 1.0- to 3.5-μm-long papillary projection on columellae, and sympodial sporangiophores. A. medulla is characterized by cylindrical to oval sporangiospores, a 1.0- to 4.5-μm-long bacilliform projection on columellae, and spine-like rhizoids. A. turgida is characterized by variable sporangiospores, up to 9.5-μm-long clavate projections on columellae, and swollen top of the projection and inflated hyphae. A. zonata is characterized by cylindrical to oval sporangiospores, a 2.0- to 3.5-μm-long spinous projection on columellae, and as many as eight whorled sporangiophores. Phylogenetic analyses based on sequences of internal transcribed spacer rDNA and D1–D2 domains of LSU rDNA support the novelty of these four species within the Absidia. All new species are illustrated, and an identification key to all the known species of Absidia in China is included.